Acessibilidade em espaços públicos: o caso do centro de Maceió - Lanverly, Larissa Costa Silva (2010)
This work deals with the accessibility of persons with disabilities and reduced mobility in public spaces in cities. From the case study of the central area of the city of Maceió, capital of Alagoas state, it discusses accessibility in urban areas using methods and techniques of the Post Occupancy experimental (APO). There has been reference to the understanding of the key theoretical and conceptual aspects of the theme of accessibility and universal design as well as the laws and standards in Brazil, particularly the Technical - NBR 9050 - implemented in Brazil in 1985 and their amendments, determining important parameters for accessibility projects. The article discusses the strengths and weaknesses of the study area from an assessment that involves different groups of users, to then make recommendations that can guide future interventions and enhance public spaces in central areas for individuals with disabilities and reduced mobility with an inclusive and sustainable way.